Distribution of airway narrowing responses across generations and at branching points, assessed in vitro by anatomical optical coherence tomography - Noble, P.; McLaughlin, R.; West, A.; Becker, S.; Armstrong, J.; McFawn, P.; Eastwood, Peter; Hillman, D.; Sampson, D.; Mitchell, H. (BioMed Central, 2010)
Background: Previous histological and imaging studies have shown the presence of variability in the degree of bronchoconstriction of airways sampled at different locations in the lung (i.e., heterogeneity). Heterogeneity can occur at different airway generations and at branching points in the bronchial tree. Whilst heterogeneity has been detected by previous experimental approaches, its spatial relationship either within or between airways is unknown.Methods: In this study, distribution of airway narrowing responses across a portion of the porcine bronchial tree was determined in vitro. The portion comprised contiguous airways spanning bronchial generations (#3-11), including the associated side branches. We used a recent optical imaging technique, anatomical optical coherence tomography, to image the bronchial tree in three dimensions. Bronchoconstriction was produced by carbachol administered to either the adventitial or luminal surface of the airway. Luminal cross sectional area was measured before and at different time points after constriction to carbachol and airway narrowing calculated from the percent decrease in luminal cross sectional area.Results: When administered to the adventitial surface, the degree of airway narrowing was progressively increased from proximal to distal generations (r = 0.80 to 0.98, P < 0.05 to 0.001). This 'serial heterogeneity' was also apparent when carbachol was administered via the lumen, though it was less pronounced. In contrast, airway narrowing was not different at side branches, and was uniform both in the parent and daughter airways.Conclusions: Our findings demonstrate that the bronchial tree expresses intrinsic serial heterogeneity, such that narrowing increases from proximal to distal airways, a relationship that is influenced by the route of drug administration but not by structural variations accompanying branching sites. © 2010 Noble et al; licensee BioMed Central Ltd.